Power of Cognition: How Dysfunctional Cognitions and Schemas Influence Eating Behavior in Daily Life Among Individuals With Eating Disorders - Legenbauer, Tanja; Radix, Anne Kathrin; Augustat, Nick; Schütt-Strömel, Sabine (Frontiers in Psychology, 2018)
Eating disorders (EDs) are characterized by marked cognitive distortions and maladaptive schemas. Cognitive models of EDs highlight the direct impact of cognitive dysfunctions on eating-related disturbances, insofar as specific cognitive contents such as thoughts about diet rules and food or loss of control may trigger disturbed eating behavior. Moreover, early maladaptive schemas that reflect perfectionist standards and relate to achievement and performance seem to be associated with disturbed eating, e.g. via their impact on situation-specific appraisals. However, so far, no study has investigated these assumptions. Hence, the present study sought to demonstrate whether and how cognitive content exerts an impact on eating behavior in daily life, and whether maladaptive core schemas impact the occurrence of binge eating via dysfunctional ED cognitions in eating-related contexts. N = 29 females with Bulimia Nervosa (BN), n = 31 females with Binge Eating Disorder (BED) and n = 30 female controls without EDs (NC) participated in the study. All participants received a handheld computer for a 48-hour period to capture antecedents of disturbed eating behavior in daily life. Event-sampling (meals, binge eating, purging, stressful situations) and signal-sampling (five times a day) methods were applied. EMA included a short questionnaire to assess dysfunctional cognitions and level of craving and to capture information about situational contexts. Early maladaptive schemas were assessed using a short version of the Young Schema Questionnaire at baseline. The main results showed specific patterns of dysfunctional eating-related cognitions for BED and BN. Binge eating was predicted by thoughts about loss of control (positively) and dietary restraint (negatively). For meal situations, no significant differences between the two ED groups emerged. All three domains exerted indirect effects on craving via thoughts about ‘eating/loss of control’, whereas neither a direct nor an indirect effect emerged regarding thoughts about ‘dietary restraint’. These results fit well with previous studies and support cognitive models of EDs; schema therapeutic approaches may be a valuable contribution to enhance treatment of EDs. Further studies should explore whether the findings from emerging adulthood can be generalized to younger age groups.